Egg Quality and Chemical Components of Arabic and Commercial Chicken Enriched with Omega 3 During Storage - Zakiah Wulandari; Iman Rahayu Hidayati; Risha Andriani (Faculty of Animal Science Universitas Brawijaya, 2022)
The aim of this research was to study the effect of storage periode and egg types on quality and chemical components of DHA enriched egg. One hundred and twenty six each control and DHA enriched eggs used in this research. The research had been implemented using the general linier models procedure included the storage period and eggs treathment and interaction between these factors, comparison test is calculated based on Tukey Test. Internal egg quality was observed, eq,: weight of egg, yolk color and water activity.Â Internal quality were influenced by egg type.Â Albumen height and haugh unit value were influenced by both type of chicken and storage periods. Fat and cholesterol levels of egg DHA-rich Arabic and commercial were lower than those of control. However, the percentage of omega-3 fatty acids components were higher in DHA-rich Arabic and commercial than in control eggs.